Theoretical and exploratory research on sustainability mental model of the public in China: based on a typical survey in Guangdong province. Issue 2 (3rd April 2017) - Long, Chengzhi; Lin, Jing
ABSTRACT: This article aims to investigate the public's sustainability mental model (SMM), which can reveal the sustainability dilemma from the public respective, other than enterprise or government. In this article, SMM is defined as one's cognitive structure, thinking mode, and behavior tendency when someone deals with sustainability issues. After theoretical analysis, the authors developed reliable and valid measures systematically and conducted a typical survey with 581 participants from college students' families in Guangdong province in China. Based on those samples, the author used the exploratory factor analysis and confirmatory factor analysis to construct a measurement model of SMM, which includes three dimensions, i.e. sustainable cognition, sustainable thinking, and sustainable behavior intention. According to SMM survey and clustering analysis, the results indicate that SMM of those participants is inactive. Even though those samples do not represent the whole country comprehensively, but this survey was sampled typically and they came from around China. So, the authors consider the SMM scores can reflect Chinese people to some extent, leading to the assumption that SMM of Chinese people is not active presently.